Potensi Plant Growth-Promoting Bacteria Menekan Cucumber mosaic virus pada Tanaman Mentimun: The Potential of Plant Growth-Promoting Bacteria to Suppress Infection of Cucumber mosaic virus on Cucumber Plants - Ridho, Muhammad Arif; Rahma, Haliatur; Martinius; Trisno, Jumsu (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2025)
The Potential of Plant Growth-Promoting Bacteria to Suppress Infection of Cucumber mosaic virus on Cucumber Plants Mosaic disease caused by Cucumber mosaic virus (CMV) is one of the main diseases of cucumber plants, and is economically important. Plant growth-promoting bacteria (PGPB) are plant root organisms currently being developed as biological agents. This research aims to obtain the best PGPB that can suppress the development of CMV in cucumber plants. This research used a randomized block design with nine treatments and five replications. The treatments consisted of several isolates of PGPB (Serratia marsescens AR1, Alcaligenes faecalis AJ14, Stenotrophomonas pavanii KJKB 5.4, Pseudomonas fluorescens LPK1–9, Bacillus cereus AJ 34, and S. maltophilia LMTSA 5.4), orthohydroxybenzoic acid (salicylic acid), positive control, and negative control. Application of PGPB was conducted through seed treatment of cucumber seeds for 15 minutes before planting. The mosaic virus was mechanically inoculated on cucumber cotyledons seven days after planting. The variables observed were the development of mosaic disease and the growth of cucumber plants. Virus detection using specific primer pair CMV-IF/CMV-IR showed that the virus that infected cucumber plants had 98.3% similarity to the CMV isolate originating from India with accession number KJ874248.1. Pseudomonas fluorescens LPK1-9 is the best bacteria for slowing the incubation period, reducing the percentage of infected leaves, and reducing the severity of mosaic disease on cucumber plants. None of tested PGPB isolates that has the potential to increase the growth of CMV-infected cucumber plants. Therefore, further studies are needed on the effectiveness of the PGPB, such as improving how PGPB is applied.